2020
DOI: 10.21873/invivo.11986
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein/Albumin Ratio as a Predictive Factor for Gallbladder Carcinoma

Abstract: Background/Aim: The C-reactive protein (CRP) to albumin ratio (CAR) is associated with outcomes in patients with sepsis. We aimed to evaluate the significance of preoperative CAR in therapeutic outcomes after gallbladder carcinoma (GBC) resection. Patients and Methods: Fifty-three patients who underwent surgical resection for GBC between January 2008 and September 2019 were enrolled. We retrospectively investigated the relation between preoperative CAR and overall and disease-free survival. Results: The optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The prognostic scores of GPS and CAR are based on the CRP and albumin levels, and they may be related to inflammation and poor survival. In the past few years, CRP, GPS, and CAR have been shown to have prognostic value in patients with hepatocellular carcinoma ( Kinoshita et al, 2015 ) and gallbladder ( Utsumi et al, 2020 ), pancreatic ( Primavesi et al, 2020 ), ovarian ( Liu et al, 2017 ), esophageal ( Sakai et al, 2020 ), and gastric ( Okugawa et al, 2020 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic scores of GPS and CAR are based on the CRP and albumin levels, and they may be related to inflammation and poor survival. In the past few years, CRP, GPS, and CAR have been shown to have prognostic value in patients with hepatocellular carcinoma ( Kinoshita et al, 2015 ) and gallbladder ( Utsumi et al, 2020 ), pancreatic ( Primavesi et al, 2020 ), ovarian ( Liu et al, 2017 ), esophageal ( Sakai et al, 2020 ), and gastric ( Okugawa et al, 2020 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of in ammation, CRP synthesis is stimulated by in ammatory cytokines, while albumin synthesis is suppressed [19]. CAR therefore sensitively detects systemic in ammation, and preoperative CAR has been reported to have prognostic utility in gastric cancer [20], esophageal cancer [21], and gallbladder carcinoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…CAR has been reported to be useful in predicting disease outcomes such as sepsis [8], acute pancreatitis [9], and ulcerative colitis [10]. Furthermore, it has been reported to be a useful biomarker in various carcinomas, including gastric cancer [11], esophageal cancer [12], pancreatic cancer [13], gallbladder carcinoma [14], and ovarian cancer [15]. Both CRP and albumin, factors used in CAR, are synthesized in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Among other inflammatory parameters, CAR and AST/ALT ratios, have been used as predictive factors in many diseases and in predicting complications (Pamukcu & Duran, 2021; Sakamoto et al, 2019; Utsumi et al, 2020). In this study, CAR and AST/ALT ratios were found to be low in the group whose semen analysis significantly improved after varicocelectomy; however, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%